2016
DOI: 10.18240/ijo.2016.06.12
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral retinal non-perfusion and treatment response in branch retinal vein occlusion

Abstract: Peripheral retinal non-perfusion in patients with BRVO associates significantly with intravitreal ranibizumab injections in patients with BRVO and macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In another study of 33 patients with BRVO, baseline central subfield thickness was 564 µm among those with between 50 and 100 fields of peripheral retinal non-perfusion compared to 373 µm among those with 0–49 fields of non-perfusion [52].…”
Section: Impact Of Retinal Non-perfusion On Disease Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study of 33 patients with BRVO, baseline central subfield thickness was 564 µm among those with between 50 and 100 fields of peripheral retinal non-perfusion compared to 373 µm among those with 0–49 fields of non-perfusion [52].…”
Section: Impact Of Retinal Non-perfusion On Disease Manifestationsmentioning
confidence: 99%
“…The extent of retinal non-perfusion may correlate with the final visual acuity in RVO. In a study of 53 patients with BRVO, patients with greater retinal non-perfusion (50 to > 100 fields) had final best-corrected visual acuity (BCVA) of 34.76 ETDRS letters, whereas those with smaller areas of retinal non-perfusion had BCVA of 40.63 letters [52].…”
Section: Impact Of Retinal Non-perfusion On Treatment and Follow Upmentioning
confidence: 99%
“…The management of macular edema secondary to branch retinal vein occlusion has greatly improved in recent times with the introduction of a therapy based on intravitreal injection of antivascular endothelial growth factor (VEGF) molecules and steroids [69]. Patient outcomes even with identical treatments can be vastly different due to disease, and patient heterogeneity prognostic factors for BRVO include patient age [70], baseline visual acuity and retinal thickness [51, 71, 72], early response to treatment [70], duration of macular edema [73, 74], posterior vitreous detachment [75], OCT characteristic [7678], cytokine level [34, 79], central retinal sensitivity [80], leaking capillaries and microaneurysms in the perifoveal capillary network [60, 81, 82], retinal pigment epithelium (RPE) integrity [83, 84], serious retinal detachment [85], and subretinal hemorrhage [86]. Some of these prognostic factors are still controversial.…”
Section: Treatmentmentioning
confidence: 99%
“…We previously reported that peripheral retinal nonperfusion correlates significantly with intravitreal ranibizumab injections in patients with BRVO and macular edema. 33 Rehak et al 34 evaluated 22 CRVO patients in a randomized clinical trial and suggested the selective laser photocoagulation of peripheral areas of nonperfusion may further improve the visual outcome and decrease the number of needed ranibizumab reinjections in CRVO patients.…”
Section: Discussionmentioning
confidence: 99%